Digital Financial Recording System for Culinary MSMEs - Sepbeariska Manurung; Nelly Ervina; Musa Fernando Silaen; Liper Siregar; Christine Dewi Nainggolan; Christine Loist (TGO Journal of Community Development, 2026)
This study aims to analyze the effectiveness of implementing a simple digital financial recording system in enhancing financial transparency and decision-making in culinary Micro, Small, and Medium Enterprises (MSMEs). The study was conducted at Lynn’s Kitchen, a growing culinary MSME facing challenges in unstructured and manual financial management. A community-based intervention approach was applied through pre-survey, training sessions, on-site mentoring, and continuous monitoring. The results show significant improvements in financial literacy and technical skills. Participants’ understanding of basic accounting increased from 25% to 82%, while their ability to operate the digital recording system reached 85% with an accuracy level of 90%. In addition, 80% of participants were able to independently prepare simple financial reports. The implementation also had a direct impact on business practices, where the owner began making data-driven decisions related to pricing strategies and cash flow planning. This study demonstrates that a simple and accessible digital financial recording system, combined with intensive mentoring, can effectively improve financial transparency and support better decision-making in small-scale culinary MSMEs.